Situation Report: Hungary, 28 April 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Police Flex Their Muscles / by Steven Koppany New Press Law Approved by National Assembly / by Judith Pataki Party Responds to Gorbachev's Call for a "Principled Cadre Policy" / by Steven Koppany Innovations to the Catholic Church Hungary's Treatment of Its Ethnic Romanians / by Edith Markos Ministry of Education Considers Imposing University Tuition / by Judith Pataki